Pemodelan Faktor-Faktor Kemiskinan di Indonesia Menggunakan Pendekatan Regresi LASSO - febriani, widya (Universitas PGRI Semarang, 2026)
In September 2024, the percentage of poor people in Indonesia reached 8.57 percent. This figure shows a decrease of 0.46 percentage points compared to March 2024. However, this poverty rate is still far from the national target. This study aims to analyze the factors that influence the percentage of poor people (P0) in order to provide a reference for the government to optimize policies on the dominant factors that have a strong impact on the percentage of poor people (P0). The research method uses LASSO regression due to the high multicollinearity problem in the data used. The analysis results show that the poverty depth variable (P1) and poverty severity variable (P2) have a dominant influence on the percentage of poor people (P0). The coefficient of determination value of 95% on the training data and 96% on the testing data indicates that the model has a very good ability to explain the percentage of poor people (P0).